Qualidade físico-química e microbiológica da água do Rio Quaraí - Rosa, Ketlien Vargas da (2017)
This work consists in the study of the water quality of the Quaraí River, which involves four municipalities, drains about 6,557.08 km² and divides waters between Brazil and Uruguay, being reported that the basin of the Quaraí River suffers from to inappropriate use and management that occur along its extension. The objective of this project is to diagnose the quality of the Quaraí River, in the municipality of Barra do Quaraí, using physical, chemical and microbiological parameters Three collection points were delineated in the Quaraí River in the municipality of Barra do Quaraí having as reference the international bridge that links Brazil to Uruguay, being determined point 1 to the left of the bridge, point 2 below the bridge and point 3 to the left of the bridge towards the Uruguay river, were collected from March to October 2017, and analysed the physical and chemical variables such as ammonia, nitrite, air and water temperature, transparency and pH were analyzed, and in the laboratory were measured dissolved oxygen (OD), turbidity, conductivity, pH and microbiological parameters by the multiple tubes technique. From the analysis performed, the following results were obtained: the pH presented greater irregularities in point 2, where of the seven collections, in four the values were outside the standards established by the resolution of CONAMA 357/05, which may indicate nearby pollution sources. Ammonia had significant peaks at point 1 throughout the collections, which may be lethal to aquatic organisms. Nitrite, as well as ammonia, had the most significant changes at point 1, which is related to nitrification, obtaining maximum allowed in the months of June and September. Transparency was consistent with the periods of greatest fulls and lows of the river, being in the periods of full, lower transparencies, and in periods of normal or low level higher transparencies. The temperatures were consistent with the climatic aspects presented on the collection days. The values of dissolved oxygen were within the limits allowed by the resolution, however, with values below the expected. The conductivity had greater variation in the month of June in the three points, and in April at point 2, where values greater than 100u may be signs of environmental degradation. Turbidity values varied widely between the collections, but maintaining a pattern between points, with all standards presented in accordance with resolution. Microbiological analyzes show values higher than 1600 MPN/100 mL in most of the analyzes at all points, being the point 2 that presented the highest indices. From the presented, it is suggested that Quaraí River, even with non-standard indices, may be liable to domestic supply, since previously pass through conventional or advanced treatment, and thus it is classified as Class III. Also, it is concluded that water quality standards were in the most harmful state during the spring, both in microbiological and physical-chemical factors.